PENGARUH ACFTA TERHADAP IKLIM INVESTASI DAN PENGUSAHA LOKAL DI INDONESIA - CRISANDY WASONO, RESTA Crisandy (Jurnal Akuntansi AKUNESA, 2013)
This study aims to analyze the impact of the ASEAN-China Free Trade Area (ACFTA)agreement on the investment climate and SME in Indonesia and after the ASEAN-China FreeTrade Area (ACFTA) agreement is Indonesia's economy has improved or deteriorated. Thisstudy used a qualitative descriptive method. The results of this study is the ACFTA a positiveimpact on SMEs in Indonesia, because ACFTA growing number of SMEs in Indonesia. Growthof SMEs in Indonesia have an impact on economic development. In addition, SMEs are also ableto increase the amount of state revenue.Keywords: ACFTA, Impact, SMEs, economy.